SYNTHESIZING THE SDG 3: INTERNATIONAL COOPERATION ON THE ETHICS OF GLOBAL HEALTH TOWARD 5.0 SOCIETY - Ananda Putra, Nyphadear Tiara Scoorpy; Satria, Randhi; Sri Hidayati, Siti Hajar; Sarr, Ebrima; Mohd Ghazali, Ezatul Marini binti (JURNAL AL-IJTIMAIYYAH, 2024)
Global health ethics tackles the complex ethical dilemmas associated with healthcare policies and practices at a global scale, focusing on key principles such as equity, solidarity, and beneficence. These principles are essential for fostering health and well-being, particularly in low- and middle-income countries where healthcare access remains limited. The aim of this study is to examine the ethical dimensions of global health, highlighting the interconnectedness of health outcomes and the collective responsibility of nations and communities in addressing global health inequities. The study employs a qualitative field research approach, utilizing in-depth interviews and secondary data analysis to assess the application of these ethical principles in practical settings. Data were gathered from key figures in the global health sector, including policymakers, healthcare professionals, and representatives from international organizations. The results underscore the importance of incorporating social determinants of health, such as poverty, education, and housing, into global health strategies. The research further emphasizes the crucial role of robust health systems, human rights, and social justice in achieving equitable health outcomes. Additionally, it illustrates the increasing significance of global health ethics in a 5.0 society, where sustainability, justice, and equity are central goals. The study advocates for collaborative efforts among global health stakeholders and stresses the need for a comprehensive approach to reduce health disparities and enhance the well-being of all populations.